ANALISIS PENGARUH WAKTU DAN JARAK PERJALANAN KAPAL TERHADAP BIAYA LOW SULPHUR SURCHARGE - Gita Kurnia; Maulida Nawadir (Jurnal Manajemen Industri dan Logistik, 2021)
AbstractThe danger of ship emission caused by HFO (Heavy Fuel Oil) fuel type has become a serious matter due to its high containment of sulphur as much as 3.50% m/m. The IMO (International Maritime Organization) took action on this problem by releasing new regulation to limit sulphur in the ship fuel as low as 0.50% m/m. This regulation leads to an additional tariff called the LSS (Low Sulphur Surcharge). As an impact, shipping companies charge this fee to customers and ocean freight forwarders, hence there is an increase of the total shipping charges. Meanwhile, the dominant variable which determines the LSS charge amount is not yet known, so it is still uninformative for the public and the academic field. The purpose of this study is to analyse which variable gives the most influence on the amount of the LSS tariff. By using multiple linear regression method, the study finds that the shipping distance variable is the dominant variable with a contribution value of 86.48% and has positive relationship with the LSS tariff. On the other hand, though the voyage time also has influence on the tariff, the effect is weak and it shows negative relationship with the LSS tariff.